Thermal, mechanical, and rheological characterization of polypropylene/layered double hydroxide nanocomposites - Lonkar, Sunil P.; Therias, Sandrine; Leroux, Fabrice; Gardette, Jean Luc; Singh, Raj Pal (Polymer Engineering and Science, 2012)
Polypropylene (PP)/organomodified layered double hydroxide (LDH) nanocomposites were prepared in order to examine the influence of LDH content on thermal, mechanical, and rheological properties. The nanostructure examinations by X-ray diffraction (XRD) and transmission electron microscopy (TEM) confirmed the exfoliated/intercalated dispersion of LDH. Incorporation of the LDH resulted in a noteworthy improvement in the thermal stability of PP. It was shown that the addition of LDH contributed to the reinforcement effect by increasing the elastic modulus. The mechanical performance, as evaluated by stressstrain curves, reveal that PP/LDH hybrid materials showed significant contribution toward increment in elastic modulus, tensile strength but at the expense of impact strength. The rheological response showed a strong influence of LDH particles on the flow behavior of the PP/LDH melt which resulted in enhancement of storage, loss of moduli, and complex viscosity of nanocomposites. Therefore, the nanocomposites have higher moduli but better processibility compared with pure PP. Overall, the results indicated that the LDH particles in nanometer size might act as potential reinforcing agent for polypropylene. POLYM. ENG. SCI., 52:20062014, 2012. (c) 2012 Society of Plastics Engineers